Peranan Audit Pemasaran Pada Usaha Minuman Yotta di Makassar Cabang Pettarani - Sangkala, Masnawaty (Journal of Economic Education and Entrepreneurship Studies, 2023)
This study aims to determine information related to the application of Marketing Audits in the Yotta beverage business in Makassar. The method used in this research uses quantitative research methods with the data used obtained using questionnaires and library data. The results of this study indicate that the Yotta beverage business continues to innovate and put more effort into organizing sales strategies so that it can capture market share.